Den svenska dagpressens särskilda ställning är inte tillfäldigheternas spel… Dagstidningsmarknaden i dagens Sverige - Dunajska, Maria (Folia Scandinavica Posnaniensia, 2007)
The Swedish newspaper market has been traditionally very strong both in terms of circulation and advertising revenues. Thus, the country has always been placed close to tbe top in newspaper consumption in Europę. The following article is an attempt to give an overview of the newspaper market in toda/s Sweden, with its traditional division and major features. Special emphasis is laid on those phenomena which contributed to Sweden's uniąue position on the European market, namely the fact that newspaper circulation is generally very high, newspapers are mainly locally or regionally based, there is a high level of readership, and, what is worth noting, papers are read among all social groups. Moreover, most of the moming newspapers are sold by subscription and offer early moming borne delivery, which seems to be remarkably effective. The closing part of the article deals with the economic market, focusing mostly on the advertising revenues as well as concentration of the newspaper market.